STUDY OF ORGANIZATIONAL AND INNOVATIVE FUNDAMENTALS ECONOMIC SECURITY OF ENTERPRISES - KOLESNIKOV, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is concerned with studying the theoretical and practical foundations of the organisational and innovative aspect of economic security enterprise, which defines the ways and means of formation, distribution, coordination and control of resources, functions, processes, structures, culture, motivation, communication and other elements of the organisational system of enterprise with a view to ensuring its innovative activity, adaptability, flexibility and openness. The article defines the essence, structure, functions, principles, methods and models of the organisational and innovative aspect of economic security of an enterprise. Particular attention is paid to the role of innovation as an important tool for improving the economic security the enterprise, as well formation of an organisational culture aimed at innovative development. The article contains the results of analysis of current state and trends in the development of the theory and practice of economic security management, as well as examples of application of the proposed methods and tools in practice.